The Effect Of Using Classcraft To Improve Students’ Learning Motivation In Reading Narrative Text - Zulqarnain Zikraan, Nuryella (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
Based on the researcher observation, it was found that some of the students learning motivation in reading a complex and long story. The major of the problem faced by them was found not feel motivated to learn in reading activity, and cannot answer the question after reading the Narrative Text. The design of this research was Quasy-Experiment. The researcher used cluster sampling that consist of 35 students in experiment class and 32 students in control class. The researcher gave pre-test to both classes. Then the researcher does the treatment by using Classcraft Application only in experiment class, and using conventional teaching in control class. Finally, the researcher gave post-test to both classes to know the different effect output score test between experiment class and control class. The technique of data collecting was a test and questionnaire. The technique of data analyzing data, the researcher used sample paired t-test formula by using SPSS 22. After analyzing the data, the researcher found that there is a significant effect of using Classcraft Application to improve students’ learning motivation in reading narrative text